DOI: 10.31357/fmscmst.2013.00247
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Usage of Internet Banking in Sri Lanka: The Case of Local Private Commercial Banks in Colombo District

Abstract: According to traditional banking, in order to carry out banking transactions customers are suppose to undergo time wasting, tedious process by visiting branches. At the same time to fulfill customer requirements bank has to expand its branch network with all additional expenditure. Financial institutions can save considerable operating and marketing costs by encouraging their clients to use internet banking. But still Internet banking usage is at primary stage. Therefore the purpose of this study is to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…On the topic of Internet banking as one of the self-banking channels, most scholars have tried to find the determinants of the adoption and usage of internet banking. In line with the results of this study, they also found that there is a significant effect of ease of use on the adoption or usage of selfbanking (Perera, 2013, Jayasiri, Gunawardana and Dharmadasa, 2016and Rajapakse, 2017. The ease of use has a significant effect not only on internet banking but also on the other self-banking channels such as mobile banking and ATM banking.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…On the topic of Internet banking as one of the self-banking channels, most scholars have tried to find the determinants of the adoption and usage of internet banking. In line with the results of this study, they also found that there is a significant effect of ease of use on the adoption or usage of selfbanking (Perera, 2013, Jayasiri, Gunawardana and Dharmadasa, 2016and Rajapakse, 2017. The ease of use has a significant effect not only on internet banking but also on the other self-banking channels such as mobile banking and ATM banking.…”
Section: Discussionsupporting
confidence: 88%
“…The correlation analysis of the study revealed that there was a weak positive relationship between perceived risk and adoption of self-banking. That result was in line with Perera (2013). However, the results of the regression analysis revealed that there is no impact of risk on the adoption of self-banking.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation